2018
DOI: 10.1007/s00421-018-3974-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue does not alter performance or neuromuscular fatigue development during self-paced exercise in recreationally trained cyclists

Abstract: Mental fatigue induced by prolonged cognitive task does not impair performance nor alter the degree of central and peripheral fatigue development during self-paced exercise in recreationally trained cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 61 publications
7
26
1
1
Order By: Relevance
“…In this study we found that a sustained attention task that induced mental fatigue had no effect on muscle twitch properties as a single or dual-task, indicating our contraction protocol did not induce muscular fatigue. This finding is also consistent with previous investigations in which inducing mental fatigue did not change muscle contractile properties of the knee extensors (Pageaux et al, 2013;Silva-Cavalcante et al, 2018). There was a significant main effect of time for M-wave amplitude, however, given post hoc analysis did not demonstrate significant change over time, this difference is likely not significant.…”
Section: M-wave and Muscle Twitch Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…In this study we found that a sustained attention task that induced mental fatigue had no effect on muscle twitch properties as a single or dual-task, indicating our contraction protocol did not induce muscular fatigue. This finding is also consistent with previous investigations in which inducing mental fatigue did not change muscle contractile properties of the knee extensors (Pageaux et al, 2013;Silva-Cavalcante et al, 2018). There was a significant main effect of time for M-wave amplitude, however, given post hoc analysis did not demonstrate significant change over time, this difference is likely not significant.…”
Section: M-wave and Muscle Twitch Propertiessupporting
confidence: 92%
“…There was a significant main effect of time for M-wave amplitude, however, given post hoc analysis did not demonstrate significant change over time, this difference is likely not significant. No change in M-wave amplitude after a mentally fatiguing task is consistent with the findings of others (Pageaux et al, 2013;Silva-Cavalcante et al, 2018). These results suggest that exercise performance decrements after a mentally fatiguing task are not likely due to impaired contractile properties, and thus more central processes are contributing.…”
Section: M-wave and Muscle Twitch Propertiessupporting
confidence: 90%
“…In this study, participants in the mental fatigue condition reached exhaustion sooner in a cycling test and rated a higher RPE. Subsequently, this literature has grown considerably over the last few years, with some studies replicating Marcora et al's (2009) findings (e.g., Head et al, 2016;MacMahon, Schücker, Hagemann, & Strauss, 2014;Pires et al, 2018) and others reporting null effects (Holgado, Troya, Perales, Vadillo, & Sanabria, 2020;Silva-Cavalcante et al, 2018;Van Cutsem, De Pauw, et al, 2017). This discrepancy could be accounted for by several factors that deserve closer examination.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, McMorris et al (2018) biases. Together with this potential publication bias, the results from the empirical studies should be interpreted with caution for the following reasons: first, sample sizes are generally low (less than 20 participants) which may lead to overestimation of effect sizes; second, the experimental and control conditions usually varied in several components, such as the duration of the interventions (Martin et al, 2016) or performing a cognitive task versus doing nothing in the control condition (Martin et al, 2016;Penna et al, 2018;Pires et al, 2018;Silva-Cavalcante et al, 2018;Staiano et al, 2018).…”
Section: Mental Fatigue Before Self-paced Exercisementioning
confidence: 99%